The Effect of Refrigerant Pressure on The Accommodation Cooling System on The MV. Meratus Medan 1 Ship - Riko Dwi Cahyo; Azis Nugroho; Shofa Dai Robbi; Antonius Edy kristiyono; Wulan Marlia Sandi (International Journal of Science and Environment (IJSE), 2026)
The ship's accommodation cooling system is crucial for crew comfort, but often experiences decreased performance due to suboptimal refrigerant pressure. This study aims to analyze the effect of refrigerant pressure on the performance of the accommodation cooling system on the MV. Meratus Medan 1. Using a descriptive quantitative approach with primary data from observations and interviews with second engineers, as well as secondary data from log books. The population is operational data from one year of sea practice, purposive samples from daily measurements. Instruments include a manometer and SPSS for regression analysis (F, t, R² tests). The results show R² 0.960, F test sig. 0.000, and the equation Y = 122.644 – 1.435X1 – 4.712X2, confirming the significant effect of low (X1) and high (X2) pressure on room temperature (Y). The conclusion recommends routine PMS maintenance to prevent leaks and optimize COP, with limited generalization to normal sailing conditions.